PENINGKATAN HASIL BELAJAR PEMBELAJARAN PKN DENGAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (GI) DI SD - Rahmi, Alfi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Problems in Citizenship Education learning the teacher is still dominated by the teacher as a source of information. In addition, teachers are less precise in selecting and using learning models and teachers rarely have discussions. For that researchers took Model Cooperative Learning type Group Investigation (GI) in the hope of improving learning outcomes Civics. This type of research is used classroom action research. The study used a qualitative approach and quantitative approach. The results of this study indicate that the learning outcomes of students has increased. First cycle average result was 66.65 cognitive, and the affective is 63.6. And the second cycle increases the average being 81.9 and cognitive aspects of the affective aspect of 80.9. From the research done it can be concluded that by using a model of Cooperative Learning Group type investigation (GI) can improve student learning outcomes in the classroom teaching Civics at V SDN 20 Tigo Suku Paninjauan District. Tanah Datar. Kata Kunci: hasil belajar; PKn; group investigation (GI)